Effect of salinity on the determination of dissolved non‐reactive phosphorus and total dissolved phosphorus in coastal waters. (5th April 2022) - Hu, Nana; Tang, Qi; Sheng, Yanqing
Abstract: The salinity may affect the phosphorus (P) determination accuracy in coastal waters, especially for the dissolved non‐reactive P (DNRP) and total dissolved P (TDP). In this work, the competition mechanism between NaCl and DNRP for oxidants (K2 S2 O8, the most commonly used and recognized oxidant) was identified in different DNRP determinations. Furthermore, salinity influences on determinations of tetrasodium pyrophosphate decahydrate, glyphosate, phytic acid sodium salt hydrate, adenosine‐5′‐nomophosphate disodium, and TDP were investigated. The results indicated that approximately 10% IHP6 and AMP would be transferred to dissolved reactive P (DRP) during digestion without K2 S2 O8 . When NaCl increased from 0% to 3.5% with fresh water method, the determination of Gly + K2 HPO4 and IHP6 + K2 HPO4 decreased by 8.0% ± 0.00% and 24% ± 0.01%, respectively. In addition, the determinations of DNRPs and TDP with different salinities in natural coastal waters by fresh water method and seawater method were performed. It showed that when the salinity >5.0 PSU, the DNRPs and TDP determination results presented deviations. At a salinity of 35.0 PSU, the TDP (KH2 PO4 + Gly + IHP6 + AMP) reduction measured by two methods was more than 12.3% ± 0.46%. Furthermore, oxidants with higher digestion efficiency than K2 S2 O8 should be developed. Practitioner Points: 10% IHP6 and AMP could be transferred to DRP during digestion without K2 S2 O8 addition. Salinity affects the DNRPs determination results mainly due to competition for oxidants and complexation with metal ions. More than 12.3% TDP in coastal waters could not be measured when the salinity was 35.0 PSU. Abstract : The increase of salinity results in the decrease of the digestion efficiency of K2 S2 O8 .